Predictability of the impact of multiple stressors on the keystone species Daphnia. Issue 1 (December 2018) - Cuenca Cambronero, Maria; Marshall, Hollie; De Meester, Luc; Davidson, Thomas; Beckerman, Andrew; Orsini, Luisa
Abstract Eutrophication and climate change are two of the most pressing environmental issues affecting up to 50% of aquatic ecosystems worldwide. Mitigation strategies to reduce the impact of environmental change are complicated by inherent difficulties of predicting the long-term impact of multiple stressors on natural populations. Here, we investigated the impact of temperature, food levels and carbamate insecticides, in isolation and in combination, on current and historical populations of the freshwater grazerDaphnia . We used common garden and competition experiments on historical and modern populations ofD. magna 'resurrected' from a lake with known history of anthropogenic eutrophication and documented increase in ambient temperature over time. We found that these populations response dramatically differed between single and multiple stressors. Whereas warming alone induced similar responses among populations, warming combined with insecticides or food limitation resulted in significantly lower fitness in the population historically exposed to pesticides. These results suggest that the negative effect of historical pesticide exposure is magnified in the presence of warming, supporting the hypothesis of synergism between chemical pollution and other stressors.